2001
DOI: 10.4049/jimmunol.166.4.2505
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of CD80 (B7-1) by T Cells

Abstract: Activation of T cells usually requires two signals. Signal 1 is mediated via a peptide-MHC on the APC; signal 2 is mediated via a costimulatory molecule on the APC surface. We demonstrate here that naive CD4+ T cells actually acquire the costimulatory molecule CD80 (B7-1) from syngeneic APCs after activation. This phenomenon was demonstrated showing acquisition of CD80 by T cells from CD80/CD86 (B7-2) knockout mice, and by treating T cells with cyclohexamide to further rule out endogenous expression of CD80 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
118
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(131 citation statements)
references
References 34 publications
13
118
0
Order By: Relevance
“…Previously, it was reported that T cell-APC contact is followed by a down-regulation of TCR (25,26) and that T cell-APC interaction can cause APC-derived surface molecules to adhere to the surface of T cells (27,28). Recently, our laboratory as well as others have demonstrated the acquisition of CD80 molecules by naive and memory murine CD4 ϩ T cells via direct transfer of these molecules at the site of interaction through CD28 receptors (10,12). We further demonstrated that upon acquisition of CD80, CD4 ϩ T cells from mice could act as an APC to stimulate other T cells, thus amplifying an immune response.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Previously, it was reported that T cell-APC contact is followed by a down-regulation of TCR (25,26) and that T cell-APC interaction can cause APC-derived surface molecules to adhere to the surface of T cells (27,28). Recently, our laboratory as well as others have demonstrated the acquisition of CD80 molecules by naive and memory murine CD4 ϩ T cells via direct transfer of these molecules at the site of interaction through CD28 receptors (10,12). We further demonstrated that upon acquisition of CD80, CD4 ϩ T cells from mice could act as an APC to stimulate other T cells, thus amplifying an immune response.…”
Section: Discussionmentioning
confidence: 56%
“…However, it should be mentioned that using fusion proteins to block the CD80 on APCs might lead to steric hindrance that interferes with cell:cell conjugate formation; this might also contribute to the inhibition of CD80 acquisition by T cells. However, it should be pointed out that previously reported (12) murine studies demonstrated that CD28 is responsible for CD80 acquisition. In addition, the results of proliferation assays demonstrated that CD4 ϩ T cells, upon acquisition of CD80, can further stimulate themselves and neighboring T cells to proliferate.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The identity of the molecules acquired differs according to the target cell type [14][15][16], and mainly concerns plasma membrane molecules [4, 10,14]. Transfer via trogocytosis has clearly been shown to occur for MHC [16][17][18][19][20][21][22] and co-stimulatory molecules [16,18,19,[23][24][25], virus receptors [26], adhesion molecules [18][19][20] and lipids [4,10,15,16,26,27]. Trogocytosis has been recorded with every lymphocyte type, and its proposed role(s) differ depending on the cell type.…”
Section: Introductionmentioning
confidence: 99%